The role of connective tissue metabolic processes in the development of pathological processes at inflammation of different intensity in parodontium - V. F. Cheremisina (Kazimierz Wielki University, 2018)
The objective. To study metabolic processes in connective tissue (CT) at different intensity of inflammation in parodontium. Materials and methods. The research is conducted on the sample of oxyproline, which is one of the indicators in the study of metabolic processes in the CT. This amino-acid presents in the blood in the free state, reflects the processes of collagen degradation in the form of protein-binding oxyproline and has no unambiguous interpretation. Results. At low intensity of the imflammation in the periodontium (stomatitis and alveolitis), the synthesis and collagen degradation are in relative equilibrium, and an increase in its intensity (gingivitis and especially periodontitis) leads to its violation. Conclusions. It has been established that the CT plays an important role in the development of pathological processes in periodontal tissues. The concentration of free and peptide-linked oxyproline in serum is higher in the groups of patients with more severe periodontal inflammation (periodontitis and gingivitis).